Advances in management of movement disorders in children. Issue 7 (June 2016) - Koy, Anne; Lin, Jean-Pierre; Sanger, Terence D; Marks, Warren A; Mink, Jonathan W; Timmermann, Lars
Summary: Movement disorders in children are causally and clinically heterogeneous and present in a challenging developmental context. Treatment options are broad ranging, from pharmacotherapy to invasive neuromodulation and experimental gene and stem cell therapies. The clinical effects of these therapies are variable and often poorly sustained, and only a few of the management strategies used in paediatric populations have been tested in randomised controlled studies with age-appropriate cohorts. Identification of the most appropriate treatment is uniquely challenging in children because of the incomplete knowledge about the pathophysiology of movement disorders and their influence on normal motor development; thus, effective therapeutic options for these children remain an unmet need. It is vital to transfer the expanding knowledge of the movement disorders into the development of novel symptomatic or, ideally, disease-modifying treatments, and to assess these therapeutic strategies in appropriately designed and well done trials.